Children's Physical Self-Concept, Motivation, and Physical Performance: Does Physical Self-Concept or Motivation Play a Mediating Role? - Lohbeck, Annette; von Keitz, Philipp; Hohmann, Andreas; Daseking, Monika (Frontiers in Psychology, 2021)
The present study aimed to examine the relations between physical self-concept, intrinsic and extrinsic motivation as well as physical performance of 1,082 children aged 7 to 8. The central objective of this study was to contrast a mediation model assuming physical self-concept as mediator of the relations between both types of motivation and physical performance to a mediation model assuming both types of motivation as mediators of the relations between physical self-concept and physical performance. Physical self-concept and both types of motivation were measured by using self-reported questionnaires, while physical performance was measured with ten motor skills tests. All tests were carried out during regular school hours (8‒12am) by qualified test personnel. Beyond correlation analyses, structural equation modeling (SEM) was performed to find evidence for the predictive relations between the variables under study. Results showed that physical self-concept was significantly positively related to both types of motivation and physical performance (all p < .001). In contrast, results of SEM revealed that only physical self-concept (p < .001) and intrinsic motivation (p < .05) were significantly positively linked to physical performance. Furthermore, physical self-concept proved to significantly mediate the relations of both types of motivation to physical performance (p < .001), while only intrinsic motivation, but not extrinsic motivation, proved to significantly mediate the relation between physical self-concept and physical performance (p < .05). These results suggest that school-based or extracurricular interventions targeted at improving younger children’s physical performance only by means of an increased level of physical activity or by external factors without supporting children’s physical self-concept and intrinsic motivation may have less or no effects on their physical performance.